2015
DOI: 10.1073/pnas.1503118112
|View full text |Cite
|
Sign up to set email alerts
|

Structural asymmetry in a conserved signaling system that regulates division, replication, and virulence of an intracellular pathogen

Abstract: We have functionally and structurally defined an essential protein phosphorelay that regulates expression of genes required for growth, division, and intracellular survival of the global zoonotic pathogen Brucella abortus. Our study delineates phosphoryl transfer through this molecular pathway, which initiates from the sensor kinase CckA and proceeds through the ChpT phosphotransferase to two regulatory substrates: CtrA and CpdR. Genetic perturbation of this system results in defects in cell growth and divisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 80 publications
4
56
0
Order By: Relevance
“…On the HK side, the main element engaged in the interface is helix α1 (HK) on the DHp domain from one DesK protomer, and minor contacts with helix α2’ (HK) from the second protomer. This interface broadly resembles the one found in other TCS complexes (Casino et al, 2009; Willett et al, 2015; Yamada et al, 2009; Zapf et al, 2000) (Figure 2A).
10.7554/eLife.21422.008Figure 2.The HK:RR interface and structural variability.( A ) Structural superposition of the DesK:DesR phosphatase complex (this study, PDB 5IUN) with HK853:RR468 from Thermotoga maritima (PDB 3DGE).
…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…On the HK side, the main element engaged in the interface is helix α1 (HK) on the DHp domain from one DesK protomer, and minor contacts with helix α2’ (HK) from the second protomer. This interface broadly resembles the one found in other TCS complexes (Casino et al, 2009; Willett et al, 2015; Yamada et al, 2009; Zapf et al, 2000) (Figure 2A).
10.7554/eLife.21422.008Figure 2.The HK:RR interface and structural variability.( A ) Structural superposition of the DesK:DesR phosphatase complex (this study, PDB 5IUN) with HK853:RR468 from Thermotoga maritima (PDB 3DGE).
…”
Section: Resultssupporting
confidence: 77%
“…Further supporting that this ensemble of conformations is functionally relevant, molecular dynamics simulations of the phosphotransferase complex (Figure 2—figure supplement 2) recapitulated the gliding shifts of one partner with respect to the other, reaching the different arrangements observed in the crystal structures at different moments of the simulations (Figure 2—figure supplement 2B). Loose HK:RR association architectures can actually be observed in other TCS-related complexes (Zapf et al, 2000; Casino et al, 2009; Willett et al, 2015), suggesting it is a universal feature. This explains the considerable promiscuity reported in different TCSs in in vitro assays, if long enough incubation times are allowed for a given HK to phosphotransfer to different RRs, including surrogate partners (Skerker et al, 2005).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Previous work in the nitrogen-fixing plant symbiont Sinorhizobium meliloti demonstrated that CtrA is strongly downregulated during the early steps of symbiosis [47]. In the pathogen Brucella abortus the CckA-ChpT-CtrA-CpdR pathway was shown to be required for intracellular survival in human macrophages [48]. Therefore, precise environmental regulation of CtrA abundance and activity likely plays an important role for the diverse functions that different alphaproteobacteria perform in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments were performed at B io s afety L evel 3 (BSL3) conditions as required by the Centers of Disease Control rules and regulations governing the use of Select Agents. Growth and maintenance of strains is as previously described (25). …”
Section: Methodsmentioning
confidence: 99%